INTERFERENSI FONOLOGI BAHASA ARAB PADA KREATOR KONTEN HUNĀ AL-YĀBĀN DI PLATFORM YOUTUBE - Eka Dewi Mutiara; Arjun (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
Many content creators via platforms like YouTube share their work on social media and produce content in Arabic, including a Japanese creator, Hunā al-Yābān. In some of the uploaded videos, researchers have found indications of phonological interference. This article aims to investigate the Arabic phonetic interference in the content produced by the creators of Hunā al-Yābān on the YouTube platform. This article uses the method of listening and text analysis in its implementation. This article aims to provide a comprehensive insight into the effects of phonological interference on language production in digital environments, particularly on the YouTube platform, and its implications for non-native Arabic-speaking content creators and Arabic language educators. A total of 14 data points were analyzed using an error analysis framework from a phonological perspective. The results identified three types of phonological interference: vowel changes, consonant changes, and consonant omissions. These interferences occur when non-native speakers produce Arabic sounds using phonological patterns influenced by their first language, in this case, Japanese.